The Effect of Financial Ratio on Financial Performance with Good Corporate Governance as a Moderating Variable in Himbara Banks - Yola Dwi Afila; Rahima Br Purba; M. Irsan Nasution (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the effect of financial Ratio on financial performance with Good Corporate Governance (GCG) as a moderating variable in the State-Owned Banks Association (Himpunan Bank Milik Negara – Himbara). The financial Ratio examined in this study include Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR/KPMM), while financial performance is measured using Return on Assets (ROA). GCG is proxied by the Corporate Governance Perception Index (CGPI). The research objects consist of PT Bank Mandiri (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk, and PT Bank Tabungan Negara (Persero) Tbk during the 2020–2024 period. This study employs a quantitative approach using multiple linear regression analysis and Moderated Regression Analysis (MRA). The research data were obtained from the annual reports of each bank and official CGPI publications. The results indicate that NPL, LDR, and CAR/KPMM do not have a significant effect on financial performance (ROA) of Himbara banks. In contrast, Good Corporate Governance (GCG) has a positive and significant effect on banks’ financial performance. Furthermore, the moderating analysis reveals that GCG does not moderate the relationship between financial Ratio (NPL, LDR, and CAR/KPMM) and financial performance, indicating that GCG functions as a direct independent variable rather than a moderating variable. This study implies that strengthening the implementation of good corporate governance is a key factor in improving the financial performance of state-owned banks, while the management of financial Ratio should continue to adhere to prudential principles and operational efficiency.